Modern air defense methods and countermeasures for use in operational-tactical missiles - Mykola Bondarenko; Mykhailo Vorobei (Challenges and Issues of Modern Science)
In contemporary military contexts, operational-tactical missile systems constitute pivotal arsenals in modern warfare scenarios. To safeguard against the evolving threats posed by these systems, a continuous evolution of defensive strategies and technologies is imperative. This article delves into the multifaceted realm of missile defense, scrutinizing a spectrum of methodologies from conventional anti-aircraft systems to cutting-edge artificial intelligence algorithms. The primary objective is to explore existing methodologies aimed at protecting military assets and countering high-precision weaponry. The research encompasses an extensive review of protective mechanisms, emphasizing the efficacy of "hard kill" strategies, wherein the focus lies on neutralizing the attacking munition or its carrier. This necessitates a diverse array of defense systems, ranging from integrated military units to specialized onboard apparatus tailored for individual combat vehicles. Analysis extends to hypothetical attack scenarios on strategically vital installations, considering the deployment of military units equipped with radar systems, air defense forces, and aviation resources. Of particular note is the challenge posed by the effective scattering area of contemporary munitions, accentuated by advancements in stealth technology. Radar surveillance, exemplified by systems such as the AN/TPS-43E and AN/TPS-75, assumes paramount importance in airspace control. Defense strategies span from fighter aircraft interception utilizing long-range missiles like the AIM-54C Phoenix to the deployment of surface-to-air missile systems such as the Tor-M1. In conclusion, this comprehensive review delineates priority directions for the development of countermeasures against missile defense systems. Strategies encompass technological innovations, tactical adaptations, and experimental pursuits aimed at enhancing the resilience of military assets against evolving threats.